An Identification of Authentic Narrator's Name Features in Malay Hadith Texts - Abd Rahman, N; Alias, N; Ismail, NK; Nor, ZB; Alias, MNB (IEEE, 2024)
Name is regarded as important to human. A person's name can give impact to him/her either positively or negatively. It is important to recognize or match a person's name with the right person. To do this on the computer, we need to develop a rule so that the computer will be able to recognize the right name with the right person. Before developing the rule, the features about the person's name itself need to be identified. So far, there has been very little work on recognizing a person's name in the Malay texts. This research identifies features of authentic narrator's name in the Malay hadith texts. We extracted the authentic narrators' names manually from hadith texts in the purpose of identifying the features of the names. We extracted manually 455 narrator's name from 150 Malay hadith texts. From the extracted name, exist same person of narrator's name with different types of spelling. There are also many forms of the narrator's names which refers to one person. We also identify the name manner in the Malay hadith texts and added 3 more name manners. Then, we developed the rule to recognize the narrators' names in the Malay hadith texts based on the identified features.